Development of Nuclear Physics in Kyiv - I. M. Vyshnevskyi (Ядерна фізика та енергетика)
In this brief overview historically time and reasons of the beginning of the development of nuclear physics and the creation of the Nuclear Centres were considered. The attention is concentrated on the establishment and development of the Kyiv Nuclear Centre. In particular, this year marks the 60-th anniversary of the operational start of cyclotron U-120 and the 40-th anniversary of isochronous cyclotron U-240. Together with other nuclear facilities of the Institute for Nuclear Research of the National Academy of Sciences of Ukraine, namely the research nuclear reactor and electrostatic generator composed Kyiv Nuclear Centre. Outstanding scientists, who contributed greatly to nuclear science in this Centre were noted.